Role of social networks in physical and mental development of older adults - Arango Morales, Moncerrat (2018)
This research aims to analyze whether the adults in the municipalities of Monterrey and Apodaca in the state of Nuevo León (Mexico) have electronic tools that allow access and use of social networks, and detailing interaction they have with peers, family members, and institutions that have some connection, as an alternative to integration. It was used a mixed method for data collection, a sample of 435 subjects in order to ensure representativeness. From this research, it turns out that the 49.4% (215) of older adults exposes the feelings of joy as the most repeated code because they can communicate with their relatives, friends and acquaintances, get diverse information and facilitates their tasks and work. Older adults should consume Facebook. Moreover, it is concluded that seniors perceive social networks as an integral part of their being with a sense of belonging and social inclusion.